4-H Projects: Frequently Asked Questions - Joy C. Jordan (EDIS)
4HS FS 101.14, a 3-page fact sheet by Joy C. Jordan, provides basic information on 4-H projects in an FAQ format. Published by the Florida 4-H Program, November 2006.